The Role of ChatGPT and Generative AI in Shaping the Future of Islamic Teachers’ Pedagogy in Southern Pakistan - Muhammad Kashif Majeed (Journal of Islamic Studies and Education, 2025)
Generative AI tools like ChatGPT are reshaping education, yet their use in rural and religious contexts remains limited. Guided by the TPACK and Diffusion of Innovation frameworks, this quantitative study examines AI adoption and its pedagogical impact among 440 Islamic secondary school teachers in Kot Addu, Southern Pakistan. Using questionnaire data analyzed with SPSS, the study finds moderate AI adoption that supports instructional innovation and teacher–student engagement, with male teachers showing slightly higher confidence and usage than females. Despite positive effects, challenges include self-reported data bias, limited infrastructure, and cultural concerns. The findings underscore the need for targeted teacher training, culturally sensitive policies, and institutional support, while future research should explore qualitative insights and long-term educational impacts.